Electrospun Biopolyesters: Hydrophobic Scaffolds with Favorable Biological Response - Pedram, Azari; Samira, Hosseini; Belinda, Pinguan Murphy; Sergio, O. Martinez-Chapa (Journal of Public Health International, 2018)
This article reviews electrospun biopolyester scaffolds, focusing on surface hydrophobicity, cell response, and applications in tissue engineering.